Solution of the Initial Condition Problem of the Time-Domain EFIE - Ulku, H. Arda; Ergin, A. Arif (IEEE, 2013)
Marching on-in-time (MOT) solution of the time-domain electric-field integral equation (EFIE) can be corrupted with linearly increasing and constant components. This corruption is mainly caused by the inappropriate imposition of the initial conditions to the solution of EFIE. In this study, first-and second-order formulations (FOF and SOF) of the time-domain EFIE to alleviate the linear and constant corruption components will be presented. It will be shown that FOF remedies the linear component problem and SOF remedies both linear and constant component problems.
Computational Electromagnetics Workshop (CEM) -- AUG 02-05, 2013 -- Izmir, TURKEY
Keywords: Integral-Equations; Bases